Synthesis and Characterization of A Stable Extra‐Large‐Pore Zeolite with 15×12×12 Member‐Ring Channels. Issue 45 (30th June 2022) - Cai, Xianshu; Zhao, Yue; Zi, Wenwen; Jiao, Feng; Du, Hongbin
Abstract: Extra‐large‐pore zeolites have great application potential in various industrial fields, such as oil refinery, fine chemicals and biomass processing. Herein, we report the synthesis of an extra‐large‐pore germanosilicate zeolite (named NUD‐13) by using an easily obtained aromatic organic cation 1, 2‐dimethyl‐3‐propyl‐benzimidazolium as organic structure‐directing agents. NUD‐13 possesses a rare 15‐member ring extra‐large‐pore channel intersecting with two elliptical 12‐member ring channels, which is isostructural to germanosilicate zeolite GeZA synthesized by using triphenylsulfonium. The germanium in NUD‐13 can be partially substituted by acid treatment to obtain stable high silica zeolite. In addition, aluminium is added into the framework of NUD‐13 during the post‐synthesis treatment process, which provides a foundation for catalytic application. Abstract : Extra‐large‐pore germanosilicate zeolite NUD‐13 is synthesized by using an easily obtained 1, 2‐dimethyl‐3‐propyl‐benzimidazolium as organic structure‐directing agents, which possesses a rare 15×12×12‐ring pore system. The germanium in NUD‐13 can be partially substituted by post‐synthetic modifications to obtain stable high silica and acidic aluminosilicate zeolites.